Student management system for Reed Music Studios - Bui, Ha (My University, 2010)
Reed Music Studios in Onalaska, Wisconsin provides private instruction in piano, strings, flute and guitar. Most of the management activities in the studio are manual paper-based operations which are time consuming and cause many difficulties in management. The purpose of the Student Management System for the Reed Music Studios is to provide a system that helps the studio managers conduct their daily business more easily and improve the studio?s business. The daily activities include student lessons, payment for lessons, book sales and more. In addition, information about special events such as recitals conducted by the studio and participation in various competitions will also be maintained by the system?s database. The system is developed as a web-based application that provides users flexibility and convenience. Previous data maintained by the Studio was converted from Microsoft Excel and Word files to Microsoft SQL databases and normalized. This manuscript describes the design and implementation of the Student Management System and also includes the challenges and problems faced during the development and deployment.
Keywords: Music -- Instruction and study -- Wisconsin -- Onalaska.; Web site development.; Application software -- Development.; Reed Music Studios (Onalaska, Wis.).